Association between Intelligence Level and Handicap Degree in Epilepsy Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background:. Epilepsy correlates with high limitation value, disability and function loss which can give negative impact to patient’s quality of life. This negative impact correlates with either epilectic seizures (motoric, sensory and behavior) or effects of anti-epileptic drugs that can cause cognitive impairment, which in this case is intelligence aspect with handicap in epilepsy patients. We determined correlation between intelligence level and handicap degree in epilepsy patients. Methods: The research was conducted in patients of Neurological Department of Dr. Soetomo General Hospital, Surabaya, Indonesia, who met inclusion and exclusion criteria, consecutively from July 2013-December 2013. Intelligence test was conducted using Standard Progressive Matrices (SPM) test, while test on handicap degree was conducted using Subjective Handicap Epilepsy (SHE) test. Results: There were 40 research subjects (19 females and 21 males) with average age of 30.9±9.6. The average score of SHE was 70.08±16/69, while the average score of SPM was 88.53±10.34. There was a weak positive correlation and statistically significant correlation between SPM and SHE scores (r = 0.345 and p = 0.029). Conclusion: There was a correlation between intelligence level and handicap degree in epilepsy patients.
Keywords: Epilepsy, Handicap, Intelligence